Perancangan dan Pengembangan Alat Pemisah Biji Cabai Dengan Metode Quality Function Deployment - Derlini; Andi Franata (Fakultas Teknik Universitas Samudra, 2020)
Bakaran Batu Village is one of the districts in Lubuk Pakam that chilli-producing. In separating chili seeds, the farmers still use the design tools that are already available, but it is not effective if the separation is worked in large quantities. In this research, a chilli seed separator was designed with a Quality Function Deployment (QFD) method and used to get the voice of consumers and the technical characteristics that needed in designing chilli seeds separator, so that it can fulfill the need of the farmers and consumers. Voice of the customer, the design is based on eleven consumer voice attributes which are then developed into ten technical characteristics that are weighted with the House of Quality (HOQ) matrix to the stage of weighting technical characteristics, and more emphasis on work safety and user’s comfort factors.